(untitled) (KYAMC Journal, 2019)
Background: Depression is now a recognized independent risk factor of coronary artery disease. Postmyocardial infarction (MI) patients with a clinician-diagnosed depressive disorder or self-reported depressive symptoms carry a 2.0- to 2.5-fold increased relative risk of new cardiovascular events and cardiac mortality. Objective: The objective of this study was to determine the prevalence of depression among patients suffering from MI. Materials and Methods: This was a cross sectional study carried out in the department of Cardiology in collaboration with department of Psychiatry at North Bengal Medical College Hospital (NBMCH) Sirajganj, Bangladesh, during the period of July 2016 to December 2017 among purposively selected 50 patients attended the Cardiology in-patient department of NBMCH. Results: The heighest number of respondents (30%) were from 41-50 years of age group. Among the respondents, 68% were male and 32% were female. Most of them were married (80%), muslim (78%), completed higher secondary level of education (26%), businessmen (38%) and of rural background (60%). Total numbers of depression were 28 (56%), among them, 17 were males and 11 were females. Conclusion: This study reflects that post MI patients experienced significantly higher rate of depression. So we should pay attention for their cardiac management as well as to evaluate depression KYAMC Journal Vol. 10, No.-1, April 2019, Page 39-42